Demonstrative Proof in Defence of God : A Study of Titus of Bostra's Contra Manichaeos - The Work's Sources, Aims and Relation to its Contemporary Theology - Pedersen, Nils Arne, (Nag Hammadi and Manichaean Studies ;, 2004)
This volume is the first extensive study of a Christian work from the 4th century, Titus of Bostra's Contra Manichaeos , which is the only text from the early Greek Church setting out a comprehensive theodicy. The study illuminates the text's relation to contemporary theology and philosophy and interprets it in the light of the ideological conflicts between pagans, Catholic Christians and Manichaeans in the 4th century. It includes an examination of the possible Manichaean sources used by Titus, and, furthermore, a critical text study and translation of central passages in Contra Manichaeos , based both on the Greek text and the Syriac version of it.